At-thoyyib shop inventory management system - Ilias, Juliana; Kasim, Shahreen; Hassan, Rohayanti; Mahdin, Hairulnizam; Ramli, Azizul Azhar; Md Fudzee, Mohd Farhan; Salamat, Mohamad Aizi (Zibeline Internasional Publishers, 2018)
At-Thoyyib Inventory Management System is developed as an online system to facilitate inventory management that includes the entry and exit of goods in storage. The main purpose of this system development is to assist a inventory management for At-Thoyyib Shop that will be managed systematically and efficiently. From observations and interviews that have been made, the problem that has identified is, the system used in the At-Thoyyib Shop is managed manually. For example, if the inventory data were recorded using book, there are a few disadvantages that were, books is perishable, and a person can also make errors in recording the data in the book. The objective of this system is to develop a report module for data in and out of inventory and also to facilitate access of the information goods. The methodology that has been used in this developing system is waterfall model. The advantages of waterfall model are that it is easy to explain to users. Structural approach for this model of the activities of each stage and well defined. In addition, it also helps to plan and schedule a project. In conclusion, the inventory management system is developed to expedite the process of recording inventory information and improve the efficiency and accuracy to generate reports required by management.At-Thoyyib Inventory Management System is developed as an online system to facilitate inventory management that includes the entry and exit of goods in storage. The main purpose of this system development is to assist a inventory management for At-Thoyyib Shop that will be managed systematically and efficiently. From observations and interviews that have been made, the problem that has identified is, the system used in the At-Thoyyib Shop is managed manually. For example, if the inventory data were recorded using book, there are a few disadvantages that were, books is perishable, and a person can also make errors in recording the data in the book. The objective of this system is to develop a report module for data in and out of inventory and also to facilitate access of the information goods. The methodology that has been used in this developing system is waterfall model. The advantages of waterfall model are that it is easy to explain to users. Structural approach for this model of the activities of each stage and well defined. In addition, it also helps to plan and schedule a project. In conclusion, the inventory management system is developed to expedite the process of recording inventory information and improve the efficiency and accuracy to generate reports required by management.